2021
DOI: 10.1080/09669582.2021.1932933
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Instagram representations in the aviation industry

Abstract: Air transport and tourism are interdependent systems wherein idealized gender performances are shaped by organizational cultures and particular commercial interests that have implications for gendered representations. Organizations use social media spaces to influence public perceptions, yet in doing so they may (re)construct hegemonic notions pertaining to images of masculinity and femininity. This paper utilizes a feminist poststructuralist approach to deconstruct normative gendered assumptions that exist wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
1
0
1
Order By: Relevance
“…To reduce this gender gap, prior studies have indicated that feminist approaches such as mentoring among female pilots and extra learning procedures and assistance could help change their stereotypes of females in aviation (eg, Dell et al., 2018; Smith et al., 2021; Yanıkoğlu et al., 2020). The supportive environment has encouraged educators to develop collaborative and feminist pedagogies to tackle the gender disparity and influence their motivation by satisfying the psychological needs of female students.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce this gender gap, prior studies have indicated that feminist approaches such as mentoring among female pilots and extra learning procedures and assistance could help change their stereotypes of females in aviation (eg, Dell et al., 2018; Smith et al., 2021; Yanıkoğlu et al., 2020). The supportive environment has encouraged educators to develop collaborative and feminist pedagogies to tackle the gender disparity and influence their motivation by satisfying the psychological needs of female students.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Smith's research revealed stereotypes in the aviation industry, where gender normative assumptions on Instagram are formed based on interests. 29 In this context, virtual society is in a dilemma about capturing the normative messages of those Instagram accounts' parody content. This parody content is created from economic motives, which actually override gender awareness, so it is not based on gender awareness.…”
Section: The Dilemma Of Gender-stolen Comedy Contentmentioning
confidence: 99%
“…Sebagai salah satu jenis media digital, instagram memiliki kekuatan global yang dapat memainkan peran penting dalam mentransmisikan informasi yang mencerminkan masyarakat, serta dapat membentuk dan membangun masyarakat melalui informasi yang ditransmisikan di dalamnya (E. Smith et al, 2021).…”
unclassified